Metodologia para classificar redes de distribuição em categorias conforme NFPA 70E-2018 e cálculos de energia incidente do guia IEEE 1584-2018 - Santos, Gilnei José Gama dos (2020)
This work presents a methodology to classify overhead medium voltage electric power distribution networks into categories for the selection of Personal Protective Equipment (PPE) in live line activities. A category of PPE is a parameter of how much protective equipment for the thermal risk of an electric arc supports Incident Energy (EI) on its surface without causing permanent damage to its user. NFPA 70E, in its most recent version of 2018, is the standard that establishes the two methods for the identification of EI. One of the methods presented is the use of tables with a set of pre-established technical parameters to which a specific EI is assigned. The second method consists estimating the EI through mathematical modeling of a specific condition under study. To calculate the EI, among the existing methods, the methodology of calculations and incident and energy standardized in the IEEE std 1584 guide of 2018 will be covered in detail. Both the table method and the EI calculation method do not fully meet all the needs of the activities of LV, either because the tables in some conditions present results that are very conservative and needlessly oversized the PPE, or because of the need calculate the EI for each new set of factors. With the proposed methodology, it was possible to estimate the EI with greater precision in relation to the tables, and without the need to estimate the EI for each condition, providing the users with better groupings in their studies, including options such as by protection zone, feeders, substations or even a set of substations.